Aetiology of spheroidal degeneration of the cornea in Labrador. Issue 4 (April 1981) - Johnson, G J
Abstract : To determine the aetiology of spheroidal degeneration of the cornea (Labrador keratopathy), total population surveys were conducted in 5 communities in coastal Labrador and northern Newfoundland. For 4 years records were also kept on all clinic patients aged 40 or more throughout the region. Both methods gave a peak prevalence at latitudes 55 degrees–56 degrees north. The greatest severity and earliest age of onset occurred around the same latitudes. Of the proposed environmental causative agents only ultraviolet radiation, reflected from ice and snow, explains the distribution of the disease. The high cumulative UV dosage is due to the unique geographical and climatic features of the region.